2013
DOI: 10.1007/jhep03(2013)050
|View full text |Cite
|
Sign up to set email alerts
|

An algebraic approach to BCJ numerators

Abstract: One important discovery in recent years is that the total amplitude of gauge theory can be written as BCJ form where kinematic numerators satisfy Jacobi identity. Although the existence of such kinematic numerators is no doubt, the simple and explicit construction is still an important problem. As a small step, in this note we provide an algebraic approach to construct these kinematic numerators. Under our Feynman-diagram-like construction, the Jacobi identity is manifestly satisfied. The corresponding color o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 54 publications
(90 reference statements)
0
56
0
Order By: Relevance
“…terms of Kleiss-Kuijf basis [27] color-ordered scalar amplitudes A(1, σ, n) 1 multiplied by BCJ numerators n 1,σ,n [11,23] A tot = σ∈S n−2 n 1,σ,n A(1, σ, n), (1.3) This can be regarded as a result of exchanging the roles of color factors and BCJ numerators in the DDM form [20] A tot = σ∈S n−2 c 1,σ,n A(1, σ, n), (1.4) where c 1,σ,n = f 1σ 1 x 1 f x 2 σ 2 x 3 . .…”
Section: Jhep08(2014)098mentioning
confidence: 99%
See 2 more Smart Citations
“…terms of Kleiss-Kuijf basis [27] color-ordered scalar amplitudes A(1, σ, n) 1 multiplied by BCJ numerators n 1,σ,n [11,23] A tot = σ∈S n−2 n 1,σ,n A(1, σ, n), (1.3) This can be regarded as a result of exchanging the roles of color factors and BCJ numerators in the DDM form [20] A tot = σ∈S n−2 c 1,σ,n A(1, σ, n), (1.4) where c 1,σ,n = f 1σ 1 x 1 f x 2 σ 2 x 3 . .…”
Section: Jhep08(2014)098mentioning
confidence: 99%
“…An explicit construction was given by Mafra, Schlotterer and Stieberger using the pure spinor language [34]. Alternatively, it was shown that the kinematic factors can be interpreted in terms of diffeomorphism algebra [23,[35][36][37]. In a series of recent papers [38][39][40] another interesting construction was provided by Cachazo, He and Yuan (CHY) using the solutions to the scattering equations.…”
Section: Jhep08(2014)098mentioning
confidence: 99%
See 1 more Smart Citation
“…The BCJ color-kinematics duality for Yang-Mills theory [10], which is known to hold at tree-level [11][12][13][14][15] and conjectured to be valid at loop-level [16], has several interesting consequences. At tree level, it generates non-trivial relations between color-ordered partial amplitudes, so-called BCJ amplitude relations.…”
Section: Jhep11(2013)050mentioning
confidence: 99%
“…[11,12] (see also refs. [13][14][15]). The conjecture has been extended to loop level [16], where duality satisfying numerators has been found for various amplitudes in different theories [16,18,[46][47][48][49][50][51] and used in gravity constructions [19,20,52,53], though a formal proof is still an open problem.…”
Section: Jhep11(2013)050mentioning
confidence: 99%